Theatrum Mundi and site in four television Shakespeare films. Issue 1 (July 2019) - Huertas Martín, Victor
This article explores metatheatricality and site specificity in four Shakespeare television films produced by Illuminations Media: Gregory Doran's Macbeth (2001), Hamlet (2009) and Julius Caesar (2012), and Rupert Goold's Macbeth (2010). Drawing on metatheatrical theory applied to the screen and recent criticism on site-specific theatre, I explore the films as self-referential and self-conscious works embedded in environments that oppose the artifice of drama to the 'reality' of normative television film. Shakespeare's aesthetic metaphor, presented in self-contained theatrical worlds, does not depict autonomous fictions but is disrupted by outside 'reality'.